Impact of feeding fermented palm kernel cake and high dietary fat on nutrient digestibility, enzyme activity, intestinal morphology and intestinal nutrient transporters mRNA expression in broiler chickens under hot and humid conditions - Hakim, Ali Hanafiah; Zulkifli, Idrus; Farjam, Abdoreza Soleimani; Awad, Elmutaz Atta; Ramiah, Suriyah Kumari (MDPI AG, 2022)
The study aimed at determining the ileal nutrient digestibility, digestive enzyme activity, intestinal morphology, and nutrient transporters mRNA expressions in broiler chickens fed with fermented PKC (LPKC) based diets with different levels of fat supplementation under hot and humid conditions. From day 22 to 35, broiler chickens were randomly fed with either (1) 20% LPKC-based diet with 5% palm oil, (2) 20% LPKC based diet with 9.5% palm oil, (3) 20% PKC-based diet with 5% palm oil or (4) 20% PKC-based diet with 9.5% palm oil. Feeding LPKC and PKC diets at the finisher phase have not affected the nutrient’s digestibility, but a higher level of oil supplementation does. This was seconded by changes in the digestive enzyme activity, villus height, and mRNA expression of nutrient transporters in the higher level of oil-supplemented diets fed chickens. In conclusion, the inclusion of oil at 9.5% in a 20% LPKC/PKC-based diet is necessary to ensure better nutrient digestibility in chickens via improved digestive function, especially in hot and humid tropical regions.